Dark nutrient uptake at low temperature and subsequent light use efficiency by the dinoflagellate Heterocapsa triquetra. Issue 9 (20th October 2016) - Ojamäe, Karin; Peterson, Anneliis; Lips, Inga
ABSTRACT: For population growth in stratified environments, flagellates are known to migrate to the nutrient-rich water layers below the thermocline to take up inorganic nutrients and ascend to the nutrient-deficient euphotic water layer to photosynthesize. The present study investigated dark nutrient uptake at 4°C (characteristic water temperature below the thermocline in the Baltic Sea) by the dinoflagellate Heterocapsa triquetra . The recovery of photosynthetic performance and the improvement of cell growth after dark nutrient acquisition and meeting suitable light conditions were also studied. On average, the consumption of and in the absence of light at 4°C was 0.04 and 0.003 µM h −1, respectively. N:P uptake ratios were similar during dark, cold incubation and a following light–dark cycle. In the nutrient-deficient cultures, the effective photochemical yield was lowered to 36%, while it recovered to 64% after simultaneous dark incubation and nutrient addition. Increased photosynthetic efficiency yielded a 34% higher cell concentration after incubation in dark, cold, nutrient-enriched conditions in comparison to the parallel N-deficient cultures that received no nutrients. The results suggest that H. triquetra can successfully compromise between dark nutrient acquisition and the use of the internal nutrient storage for photosynthesis later in the light field.